Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.topol.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Topological graph inverse semigroups

Abstract: To every directed graph E one can associate a graph inverse semigroup G(E), where elements roughly correspond to possible paths in E. These semigroups generalize polycyclic monoids, and they arise in the study of Leavitt path algebras, Cohn path algebras, graph C * -algebras, and Toeplitz C * -algebras. We investigate topologies that turn G(E) into a topological semigroup. For instance, we show that in any such topology that is Hausdorff, G(E) \ {0} must be discrete for any directed graph E. On the other hand,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 19 publications
(37 reference statements)
1
36
0
Order By: Relevance
“…These inverse semigroups are related to various types of algebras, for instance, C * -algebras, Cohn path algebras, Leavitt path algebras and so on (see [1,2,[8][9][10][11]14]). Graph inverse semigroups have also been studied in their own right in recent years (see [2,5,7,8,12,13]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…These inverse semigroups are related to various types of algebras, for instance, C * -algebras, Cohn path algebras, Leavitt path algebras and so on (see [1,2,[8][9][10][11]14]). Graph inverse semigroups have also been studied in their own right in recent years (see [2,5,7,8,12,13]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Algebraic and topological properties of the polycyclic monoids were investigated in [19,20,5,6]. The paper [23] is devoted to topological properties of the graph inverse semigroups which are the generalizations of polycyclic monoids. In that paper it was shown that for every finite graph E every locally compact semigroup topology on the graph inverse semigroup over E is discrete, which implies that for every positive integer n every locally compact semigroup topology on the n-polycyclic monoid is discrete.…”
mentioning
confidence: 99%
“…The following Theorem extends Theorem 3 from [23] and Proposition 3.1 from [8] over the case of semitopological graph inverse semigroups. Hence each vertex a is an isolated point in G(E).…”
Section: Resultsmentioning
confidence: 56%